Reducing Tram Car's Curve-Pasing Resistance by Double Treaded Wheel Profile - Nozhenko, Olena; Hauser, Vladimír; Kravchenko, Kateryna; Loulová, Mária (Manufacturing Technology Journal, 2018)
Special attention is taking place in the environment of public transport, for which higher amount of small radius curves being applied is specific. The outcome of such operation of vehicles is an increase in vehicle's effects on the track in the rail-wheel contact resulting in increased ride resistance, creep in the rail-wheel contact patch, speeding up the process of wear in the contact pair as well as noise generation. At present, a variety of technical solutions for the vehicle bogie design as well as track designs focused on decreasing of these negative effects exists. Their use in smaller radius curves however, cannot give acceptable results and often causes complications in bogie design. The authors give a concept of creep reduction in rail-wheel contact by using double wheel tread, which doesn't require complicated bogie design. The proposed solution is supported by dynamical simulation of the tram car vehicle ride with considering of active wheel tread changes, and is also registered under Patent Application Nr. a201701589.
Keywords: wheel with double tread; vehicle curve-pasing resistance reduction; track section of small radius; creep velocitiy in wheel - rail contact